ANALISIS STRATEGI PEMASARAN TIKTOK SHOP DI ERA DIGITAL - Juwita Astuti; Rahimah Safitri; Dewi Santika Ulandari; Sinta Wulandari; Irwandi Rizki Putra (Fakultas Ekonomi dan Bisnis, 2026)
This study investigates the rising competition in e-commerce and the rapid growth of TikTok Shop as an interactive digital marketing platform. The primary research problem concerns how TikTok Shop’s live streaming feature, creative content, and influencer marketing affect consumers’ purchase intention for the Glad2Glow brand. The study aims to analyze the effectiveness of these strategies in building trust and improving purchasing decisions. A descriptive qualitative method was employed using literature review and content analysis based on secondary digital data. The findings reveal that live streaming is the most influential variable in increasing purchase intention, followed by creative content and influencer collaboration, which enhance brand credibility. Promotional tactics such as flash sales and real-time product demonstrations significantly increased sales conversion. The study recommends that SMEs continue optimizing live commerce features and strengthen authentic content to improve competitiveness in the digital marketplace.